The Dynamic Behavior of Conjugate Multipliers on Some Reflexive Banach Spaces of Analytic Functions (Contemporary Mathematics, 2024)
In this paper, we characterize the hypercyclic, mixing and chaotic conjugate multipliers on some reflexive spaces of analytic functions. Our results extend several well-known results in the existing literature. We present some nontrivial examples to show the validity of our results.
Keywords: hypercyclic operators, mixing operators, chaotic operators, conjugate multipliers